Will the real "Mrs Smith" please stand up: a critical examination of the role of vignettes in integrated service development and delivery. Issue 3 (14th August 2020) - George, Thomas; Toze, Michael; Ray, Mo; Clayton, Owen
Abstract : Purpose: To explore the use of fictitious vignettes representing older people and the extent to which they serve as an effective resource in developing service provision and transforming health and social care. Design/methodology/approach: Based on a critical review of research and academic discourse. Findings: Fictitious vignettes or case studies of older adults, such as "Mrs Smith", may be a useful means to promote communication with and between health and social care colleagues about current services and transforming or re-organising service provision. However, we argue that while there may be a role for vignettes, care should be taken in their use. The potential to "homogenise" older people into the "typical" patient personified by Mrs Smith may do very little to challenge age- based stereotypes and assumptions. Moreover, vignettes cannot match the potential value and importance of older men and women directly participating in the evaluation and development of services. Practical implications: This article argues that changing the way services are organised and delivered must be underpinned by critical reflection of the assumptions which underpin attitudes towards old age, including our tendency to define older people by chronological age and to homogenise "the elderly" into a single group. The value of participatory methods which meaningfully involve older citizens in both evaluating and planning services could contribute significantly to innovation in service development. Social implications: This paper highlights the critical importance of challenging age-based stereotypes and ageist policy and practice. Recognising old age as being characterised by diversity and difference could challenge the tendency to see old age, especially advanced old age, as an inevitable problem. Originality/value: This article offers a critical perspective on the use of vignettes.